An ultrasonic degraded polysaccharide extracted from Pueraria lobata ameliorate ischemic brain injury in mice by regulating the gut microbiota and LPS-TLR4 pathway - Yulong Zhang; Zuman Dou; Shanshan Li; Huaying Zhang; Shanshui Zeng; Xiangyu Zuo; Yu Xiao; Lingling Zhang; Zhixin Li; Qingfeng Zhu; Wenyang Zhang; Hui Niu; et al. (Ultrasonics Sonochemistry)
Ischemia brain injury is closely associated with the gut microbiota. Polysaccharides, as a typical prebiotic, have been extensively employed in stroke treatment. In our previous study, Pueraria lobata polysaccharide (PLP-3) with antioxidant activity was prepared via water extraction and alcohol precipitation combined with ultrasonic degradation. In this study, the effects of PLP-3 on ischemia brain injury and its regulatory effects on the gut microbiota were further investigated. The results demonstrated that PLP-3 effectively reduced the infarct area, improves neurological function, and alleviates neuronal damage of cerebral ischemia injury. Mechanistically, PLP-3 significantly reduces serum LPS levels in MCAO mice, inhibiting TLR-4 activation in brain tissue and thereby reducing IL-1β and TNF-α levels. Meanwhile, PLP-3 significantly repaired the intestinal barrier injury by increasing the expression of tight junction proteins (ZO-1 and Occludin) and increasing the number of goblet cells. Additionally, the structure and composition of gut microbiota in MCAO mice after PLP-3 intervention, were also significantly changed, especially the enrichment of Lactobacillus and the reduction of Corynebacterium and Staphylococcus. At the same time, short chain fatty acid, metabolites of gut microbiota, were also significantly increased and significantly correlated with the abundance of Lactobacillus. Moreover, LC-MS untargeted metabolomics revealed that PLP-3 significantly improves the intestinal metabolic profile after cerebral ischemia injury, upregulating the amino acid biosynthesis pathway and enriching amino acids such as glutamine and arginine, as well as neuroprotective flavonoids such as fisetin and liquiritigenin. These results suggested that PLP-3 could protect mice from cerebral ischemia–reperfusion injury by regulating gut microbiota and repairing gut barrier, inhibiting brain LPS/TLR4/MyD88 inflammatory pathway, therefore we provide a theoretical basis for PLP-3 as a functional food to prevent ischemic brain injury.